Features of energy supply of muscle work depending on the duration of stepwise increasing load in cyclical sports athletes - Chikov, A.; Medvedev, D.; Chikova, S.; Kolmogorov, S. (Human. Sport. Medicine, 2020)
Aim. The paper aims to study energy supply mechanisms depending on the duration of stepwise increasing load to failure in cyclical sports athletes. Materials and methods. 360 observations were made on cyclical sports athletes (biathlon, cross-country skiing) aged 18-35 years. Indicators of gas exchange, heart rate, and blood lactate levels were recorded when performing a stepwise increasing load on the treadmill with the Oxycon Pro cardiorespiratory system (Erich Jaeger, Germany). The contribution of aerobic and anaerobic capabilities depending on the duration of the load was analyzed. The sample was divided and ranked into 7 clusters based on the contribution of individual energy supply mechanisms. Results. The selected clusters differ in load execution time. The increase in the duration of load execution time from cluster to cluster is accompanied by a natural increase in the quantitative values of the estimated energy supply indicators, as well as by both unidirectional and multidirectional changes in the activity of alactate and lactate mechanisms of energy supply. Conclusion. Increasing the duration of the load to failure depends not only on the total amount of energy produced, mainly the activity of the aerobic mechanism, but also on the increase in the contribution of the alactate and lactate mechanisms of energy supply. The identified changes in clusters can be regarded as functional typological features of various energy supply mechanisms that determine physical fitness.